The role of nutritional management in preventing stroke and improving clinical outcomes - Mauluddy, Anggita Citra Resmi; Sunardi, Diana (Indonesian Nutrition Association, 2025)
Background: Stroke is a leading cause of global morbidity, mortality, and substantial economic burden. Modifiable stroke risk factors, including hypertension, dyslipidemia, obesity, and diabetes mellitus, can be effectively managed through targeted nutritional interventions. Nutritional management also supports neurological recovery and contributes to improved clinical outcomes in stroke survivors. Methods: A literature review was conducted using PubMed, MEDLINE, and EMBASE databases from the last ten years, focusing on nutritional management for stroke prevention, clinical outcomes, dietary patterns, and nutrient supplementation during post-stroke recovery. Results: Dietary strategies, including Dietary Approaches to Stop Hypertension (DASH), high intake of dietary fiber, and omega-3 fatty acids, significantly reduce stroke risk by improving cardiovascular health and decreasing inflammation. Supplementation with micronutrients such as B vitamins supports neurological and vascular function. Post-stroke nutritional issues such as dysphagia, malnutrition, sarcopenia, and pressure injuries commonly impair patient recovery. Targeted nutritional intervention, particularly adequate protein and branched-chain amino acid (BCAA) supplementation, help preserve muscle mass, enhance functional recovery, and optimize rehabilitation outcomes. Conclusions: Nutritional management plays a crucial role in both preventing stroke and improving clinical outcomes following stroke. Implementing effective nutritional strategies, together with patient education on healthy dietary practices, is fundamental for reducing stroke risk, accelerating recovery, and enhancing quality of life.